2015
DOI: 10.1097/sla.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Versus Medical Treatment of Type 2 Diabetes Mellitus in Nonseverely Obese Patients

Abstract: Metabolic surgery is superior to medical treatment for short-term remission of T2DM and comorbidities. Further RCTs should address the long-term effects on T2DM complications and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 58 publications
2
72
0
4
Order By: Relevance
“…However, the most recent review identified two RCTs and six observational studies that were conducted in patients with a BMI < 35 kg/m 2 , with five of these reporting on T2DM remission. 76 Meta-analyses of the five studies, combined with an additional three publications that included patients with mild obesity non-exclusively, gave a pooled OR of 14.1 (95% CI 6.7 to 29.9).…”
Section: Type 2 Diabetes Remissionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the most recent review identified two RCTs and six observational studies that were conducted in patients with a BMI < 35 kg/m 2 , with five of these reporting on T2DM remission. 76 Meta-analyses of the five studies, combined with an additional three publications that included patients with mild obesity non-exclusively, gave a pooled OR of 14.1 (95% CI 6.7 to 29.9).…”
Section: Type 2 Diabetes Remissionmentioning
confidence: 99%
“…73 Three reviews focused on the potential of bariatric surgery to treat T2DM in patients who were not morbidly obese (BMI < 40 kg/m 2 ). [74][75][76] The two older reviews identified one RCT of 60 patients with a BMI of 30-40 kg/m 2 who underwent adjustable gastric banding that reported on remission. 165 After 2 years, 73% of the surgery group and 13% of the controls were in remission from T2DM (p < 0.001).…”
Section: Type 2 Diabetes Remissionmentioning
confidence: 99%
“…It has been demonstrated that metabolic surgery is able to effectively regulate T2DM and obesity (31). Although innovative procedures to treat diabetes are being investigated, including the novel anti-diabetic drugs, DDP-4 inhibitor and SGLT-2 inhibitor, as well as surgical treatment by laparoscopic sleeve gastrectomy, RYGBP and IT, their precise mechanisms of action remain to be elucidated (32,33). In the present study, the effects of three surgical treatments on a rat model of T2DM were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to type 2 DM, the most important and common outcomes evaluated in clinical trials assessing for therapy effectiveness are glycemia, glycated hemoglobin (HbA1C) levels, insulin sensitivity/resistance and elimination of antidiabetic drugs (also known as "diabetes remission"). However, current therapies, other than bariatric surgery, have failed to demonstrate significant effects on the ultimate goal of type 2 DM therapy, disease remission [14,15]. Hence, this metabolic pathology is commonly referred, thus far, as an incurable and progressive disease.…”
Section: Clinical Outcomes With Vlcds In Type 2 Dmmentioning
confidence: 99%